2020
DOI: 10.3390/brainsci10040220
|View full text |Cite
|
Sign up to set email alerts
|

Double-Step Machine Learning Based Procedure for HFOs Detection and Classification

Abstract: The need for automatic detection and classification of high-frequency oscillations (HFOs) as biomarkers of the epileptogenic tissue is strongly felt in the clinical field. In this context, the employment of artificial intelligence methods could be the missing piece to achieve this goal. This work proposed a double-step procedure based on machine learning algorithms and tested it on an intracranial electroencephalogram (iEEG) dataset available online. The first step aimed to define the optimal length for signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…In more recent studies, the automatic detector using the combination of short-time energy and CNN reported in 2019 achieved a sensitivity of 91.26%, a specificity of 91.52%, and a precision of 88.67% in 2700 HFO events from 5 patients [ 21 ]. Sciaraffa et al [ 27 ] proposed a new double-step machine learning method in 2020 to detect HFOs, which achieved a sensitivity of 87.40% and a specificity of 77.60%. Guo et al [ 45 ] developed a hypergraph-based detector to automatically detect HFOs in 2021, which achieved an accuracy of 90.7%, a sensitivity of 80.9%, and a specificity of 96.9%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In more recent studies, the automatic detector using the combination of short-time energy and CNN reported in 2019 achieved a sensitivity of 91.26%, a specificity of 91.52%, and a precision of 88.67% in 2700 HFO events from 5 patients [ 21 ]. Sciaraffa et al [ 27 ] proposed a new double-step machine learning method in 2020 to detect HFOs, which achieved a sensitivity of 87.40% and a specificity of 77.60%. Guo et al [ 45 ] developed a hypergraph-based detector to automatically detect HFOs in 2021, which achieved an accuracy of 90.7%, a sensitivity of 80.9%, and a specificity of 96.9%.…”
Section: Resultsmentioning
confidence: 99%
“…In early studies, researchers mostly focused on the performance of signal detection, so in terms of dividing experimental data, most of them randomly divide training set and test set from the candidate pool [ 21 , 27 , 43 , 45 , 46 ]. In clinical application, when considering a new patient, it is desirable to transfer the a priori knowledge learned from previous existing cases to the judgment of the new patient.…”
Section: Discussionmentioning
confidence: 99%
“…Class imbalance is another issue in the feature classification step of HFO detection, which is caused by the fact that the number of HFOs is significantly less than that of fHFOs in iEEG signals [19], [31]. This class imbalance will sharply drop the classification performance since the class-imbalanced data distribution between HFOs and fHFOs biases classifiers toward the majority class (i.e., the fHFO class) [32].…”
Section: Introductionmentioning
confidence: 99%
“…These detectors often employed multi-stage algorithms, which involved the identification of putative HFO events, extraction of features from these events, and subsequent use of the extracted features to cluster oscillatory events or train the algorithm. Akin to detectors employing time-frequency analysis, variable methods were used for the initial detection of putative HFO events including energy thresholding [54,68] and multi-feature extraction [56,59]. Methods to reject false positive HFO events included analysis of the duration of the event and amplitude threshold.…”
Section: Data Mining or Machine Learningmentioning
confidence: 99%